Implementasi Augmented Reality Metode Marker dalam Pengenalan Cryptocurrency - Fera Damayanti; Fauzan Fauzan; Nurwulan Nurwulan; Rismayanti Rismayanti (Jurnal SAINTIKOM (Jurnal Sains Manajemen Informatika dan Komputer), 2023)
The variety of investments in modern times is not only limited to gold, stocks, bonds and others. Along with the times, a new type of investment instrument called Cryptocurrency has emerged. The virtual currency Bitcoin became the first Cryptocurrency to be introduced in the online market and turned out to have an impact on the world. In contrast, in this digital era there are still many people who still do not know Cryptocurrency. Augmented Reality-based Cryptocurrency introduction application where we can get to know Cryptocurrency better with a 3-Dimensional animation display where this technology combines the real world and the virtual world. The results of testing using a questionnaire of 50 participants using this application can be concluded that, before this application was introduced there were only 10% of participants who knew Cryptocurrency well and very well. After this application was introduced and used there were 76% of participants who could very well recognize cryptocurrency and 20% with participants knowing Cryptocurrency well. Therefore, the application of Augmented Reality Implementation of Marker Method in Cryptocurrency Introduction can answer the existing problems, namely with this application people can learn and know Cryptocurrency well.